OPTIMIZING NON-GOVERNMENT ORGANIZATION PERFORMANCE THROUGH ACCOUNTABILITY, GOVERNANCE, AND TECHNOLOGY - Jaka Mulyana; Holiawati; Suripto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to investigate the influence of accountability, governance, and the use of information technology on the performance of Non-Government Organizations (NGOs), with a case study on Save the Children Indonesia. The research employs a quantitative method with an associative approach, utilizing questionnaires as the data collection instrument. Out of 166 staff surveyed in June 2024, 106 questionnaires were returned, achieving a response rate of 63.86%. Data analysis was conducted using multiple regression to identify the relationships between the independent variables (accountability, governance, use of information technology) and the dependent variable (NGO performance). The results show that accountability has a positive and significant impact on NGO performance, while governance and information technology usage do not have a significant effect. These findings highlight the need for an evaluation of accountability systems and further research on other factors that might more significantly influence NGO performance.